L'amaro caso della signora di Carini - Pelleriti, Enza (Acta Histriae, 2007)
The atrocious murder of Laura Lanza La Grua, Lady Carini, during the evening of 4 December, 1563, was rapidly shrouded with mystery and concealed truths, and thus rapidly transformed into a legend. The course of popular fantasy accompanied the official memory in a kind of common conspiracy of silence in protection of the reputation of one of the most important families of the Sicilian dominant class. The event happened at the Carini Castle when Sicily was under the rule of Spanish viceroys and their feudal lords. The actors were: don Cesare Lanza, his son-in-law Vincenzo La Grua Talamanca, and wife of the latter, Laura, who seemed to have given her heart to her cousin Ludovico Vernagallo, a rich landowner. The murder of Laura Lanza can undoubtedly be described as a crime of honour. According to the old law of marital honour, which can be traced in the famous "Lex Iulia de adulteriis" of Roman law, and, as well - borrowed from the constitution of Federico II - in the rules of Ruggero II: "Si maritus uxorem in ipso actu adulterii depraehenderit tam uxorem quam adulterum occidere licebit, nulla tamen mora protracta". Therefore, a husband who surprised his wife and her lover in an obvious act of adultery could kill them both. These were the texts that Cesare Lanza, Laura's father, relied on in a statement made to King Phillip II when admitting his act. Concurrently, the story of Lady Carini also depicts the complex nature of family relations in the Sicilian society during the old regime. Examining a variety of sources that have delineated its historiographic profile, here the story will be visited again. Not only will the interpretations that followed the tragic event be presented, but the importance of judicial, literary, and visual representations, whose integrated analysis can supplement missing information in the construction of a never ascertained truth, covered with a veil of family honour and interpretations produced by a kind of anthropological romanticism will also be researched.
Keywords: 16.st.; čast; družine; kulturna zgodovina; Sicilija; zločini